Evaluation of gamma irradiation on the microbiological, phytochemicals, and aromatic profiles of sun-bleached preserved pepper (Capsicum annuum L.) - Mengyun Ouyang; Sheng Cao; Yiji Zhou; Mo Mo; Yuanfang Xu; Qiling Zhang; Yong Zhang; Chao Deng; Feng Guo; Hui Song; Yan Wang; Yiqun Huang; et al. (Food Chemistry, 2026)

The crucial roles of citrus branch compost in enhancing soil nutrients, optimizing microbial community structure, and improving fruit quality over its raw materials - Jinye Li; Songwei Wu; Jixiang Zheng; Xuecheng Sun; Qiling Tan; Chengxiao Hu (Plant and Soil, 2026)

Lake Water Depth and Nutrient Gradients Mediate Aquatic Plant Distribution via the Strength of Trait Network Associations - Guixiang Yuan; Huan Long; Jun Liu; Qiling Xie; Yaoxuan Tan; Zihui Hong; Jiahui Yue; Aimin Zhou; Hexuan Zhou; Weilin Xu; Bao Wang; Huanyao Liu; et al. (Global Change Biology, 2026)
Aquatic macrophyte responses and adaptation to water depth and nutrient gradients are of critical importance for understanding the functional ecology of lakes and their restoration when degraded. However, the role of plant trait networks (PTNs), a powerful tool for decoding trait–environment–function relationships, in mediating these adaptations remains unclear, particularly across species and community scales. We conducted cross‐scale PTN analyses at species and community levels for aquatic macrophytes, integrating assessments of phylogenetic signals and hierarchical environmental filtering. At species level, aquatic macrophytes exhibited two complementary PTN‐based adaptive strategies: trait compartmentalization to enhance stress tolerance and trait integration to optimize resource utilization. Notably, local environmental conditions (rather than phylogenetic signals) dominated the pattern of PTN metrics, highlighting the primacy of immediate habitat constraints over evolutionary relatedness in driving species‐specific adaptations. At community level, environmental filtering operated hierarchically, acting sequentially by water depth, nutrient availability, and lake morphology. PTNs further mediated the trade‐off between community diversity and productivity, providing a mechanistic link between abiotic filtering and ecosystem function. Our findings advance network theory in functional ecology by extending its application to aquatic systems, bridging longstanding gaps between terrestrial and aquatic PTN research, and offering actionable guidance for eutrophic lake restoration (e.g., by targeting PTN‐linked core traits related to nutrient adaptation). Overall, our work provides a cross‐scale framework for understanding PTN mediated adaptation of aquatic macrophytes and its implications for ecosystem management.

Role of NOX4 and GSH in Cadmium-Induced Renal Redox Homeostatic Dysregulation of Rats and APO Intervention Effect Study - Zhaofan Long; Langqiu Wei; Che Wang; Ningxi Wang; Li Song; Qiling Liu; Chuandao Shi (Biological Trace Element Research, 2026)

Analysis and evaluation of fruit traits of wild Camellia oleifera germplasm in the high-altitude region of Northwest Guizhou, China - Dongchan Sun; Chao Gao; Qiling Song; Xianqin Wan; Qimei Wang; Yanmei Nie; Luwei Zheng; Jiaying Li; Xiong Yang (New Forests, 2026)

Predictive biomarkers for valproic acid-induced hepatotoxicity in Chinese patients with epilepsy: the role of metabolites and genetic polymorphisms - Dingsheng Wen; Zhuojia Chen; Ziyi Chen; Xue Bai; Hongliang Li; Juan Chen; Qiling Dai; Guoping Zhong; Jiaming Qin; Guanzhong Ni; Min Huang; Liemin Zhou; et al. (Food and Chemical Toxicology, 2025)

Air pollution and maternal vitamin D Status: Critical time window identification and ultraviolet radiation-mediated pathways - Yuting Gong; Zeyang Li; Qiling Yao; Mengdi Zhi; Xiaoan Zhang; Junxi Zhang; Zengli Yu; Xin Zhao (International Journal of Hygiene and Environmental Health, 2025)

The carbon footprint and ecological costs of citrus production in China are going down - Jinye Li; Shanshan Liang; Xiaomin Liang; Xiaojuan Wang; Xinchen Bai; Yilin Chen; Kongjie Wu; Xiaoman Liu; Zhihao Dong; Qiling Tan; Xuecheng Sun; Chengxiao Hu; et al. (Journal of Cleaner Production, 2025)

Enhancing the applicability of sisal fibers in cement-based materials through alkali treatment and penetrating crystallization - Juhong Liang; Xianfeng Wang; Zhipeng Fu; Zhangjian Li; Limin Liang; Qiling Luo; Wujian Long (Journal of Cleaner Production, 2025)

Bisphenol A disrupts the neuronal F-actin cytoskeleton by activating the RhoA/ROCK/LIMK pathway in Neuro-2a cells - Yi Guo; Yuxin Wang; Qian Li; Qiling Liu; Xuyuan Zhang; Jiajia Ren; Chong Wang (Toxicology, 2024)

Critical windows for exposure to chemical composition of ambient particulate matter and human semen quality decline - Lingxi Wang; Qiling Wang; Yunchong Yao; Jiayi Zhou; Xiaoyan Cai; Tingting Dai; Chunying Song; Yushan Li; Fuping Li; Tianqing Meng; Huiqiang Sheng; Pi Guo; et al. (Science of The Total Environment, 2024)

Beneficial effect of residential greenness on sperm quality and the role of air pollution: A multicenter population-based study - Tingting Dai; Wei Li; Lingxi Wang; Jiayi Zhou; Kaixin Zhong; Yunchong Yao; Xiaoyan Cai; Linwei Tian; Haisheng Wu; Ting Xu; Lina Xiao; Haobo Ni; et al. (Science of The Total Environment, 2024)

Nano molybdenum trioxide-mediated enhancement of soybean yield through improvement of rhizosphere soil molybdenum bioavailability for nitrogen-fixing microbial recruitment - Qibiao Li; Kan Huang; Zhichen Liu; Xiaoming Qin; Yining Liu; Qiling Tan; Chengxiao Hu; Xuecheng Sun (Science of The Total Environment, 2024)

The pivotal role of secondary nutrients and micronutrients in regulating fruit quality and root exudates metabolism profile of citrus - Yanni Tang; Wei Lou; Xiang Yan; Shiqian Li; Pengwei Wang; Yingjie Zhou; Ting Zhan; Siming Zhang; Chengxiao Hu; Xu Wang; Hanliang Liu; Qiling Tan; et al. (Plant and Soil, 2024)

A mutant GH3 family β-glucosidase from Oenococcus oeni exhibits superior adaptation to wine stresses and potential for improving wine aroma and phenolic profiles - Yuzhu Zhao; Biying Zhang; Huawei Gu; Tongxin Xu; Qiling Chen; Jin Li; Penghui Zhou; Xueqiang Guan; Ling He; Yanying Liang; Kekun Zhang; Shuwen Liu; et al. (Food Microbiology, 2024)

Data driven multi-objective design for low-carbon self-compacting concrete considering durability - Boyuan Cheng; Liu Mei; Wu-Jian Long; Qiling Luo; Jinrui Zhang; Chen Xiong; Yuqing Shu; Zhangjian Li; Song Gao (Journal of Cleaner Production, 2024)

Adverse effects of bisphenol A and its analogues on male fertility: An epigenetic perspective - Xinyi Deng; Sihan Liang; Yuqian Tang; Yingxin Li; Ruijun Xu; Lu Luo; Qiling Wang; Xinzong Zhang; Yuewei Liu (Environmental Pollution, 2024)

Tigecycline-resistance mechanisms and biological characteristics of drug-resistant Salmonella Typhimurium strains in vitro - Lin Li; Longbo Wang; Shuo Yang; Yanfang Zhang; Yiming Gao; Qianyu Ji; Linran Fu; Qiling Wei; Feifei Sun; Shaoqi Qu (Veterinary Microbiology, 2024)

Designed CoSe2@ZnIn2S4 large area 2D/2D Schottky junction for efficient photo-utilization hydrogen evolution and biomass oxidation - Hongjie Qin; Weijie Zhang; Qiling Zheng; Chuanlin Li; Xixi Zhang; Na Li; Penghui Zhang; Hongxia Bu; Shouwei Zhang; Xijin Xu (Chemical Engineering Journal, 2023)

Sperm quality decline associated with gaseous pollutant exposure: Evidence from a large cohort multicenter study - Xiaoyan Cai; Haobo Ni; Qiling Wang; Tingting Dai; Lingxi Wang; Chunying Song; Yushan Li; Fuping Li; Tianqing Meng; Huiqiang Sheng; Lina Xiao; Ting Xu; et al. (Journal of Hazardous Materials, 2023)

Association between exposure to ambient air pollution and semen quality: A systematic review and meta-analysis - Ruijun Xu; Yanling Zhong; Rui Li; Yingxin Li; Zihua Zhong; Tingting Liu; Qiling Wang; Ziquan Lv; Suli Huang; Yong-Gang Duan; Xinzong Zhang; Yuewei Liu (Science of The Total Environment, 2023)

Exosomes Derived from Human Amniotic Mesenchymal Stem Cells Facilitate Diabetic Wound Healing by Angiogenesis and Enrich Multiple lncRNAs - Shangfeng Fu; Hongyan Zhang; Xiancai Li; Qiling Zhang; Chunyan Guo; Keqing Qiu; Junyun Feng; Xiaoxiao Liu; Dewu Liu (Tissue Engineering and Regenerative Medicine, 2023)

Modeling fertilization impacts on nitrate leaching and groundwater contamination with HYDRUS-1D and MT3DMS - Han Zhang; Ruxing Yang; Shanshan Guo; Qiling Li (Paddy and Water Environment, 2020)

Groundwater pollution source apportionment using principal component analysis in a multiple land-use area in southwestern China - Qiling Li; Han Zhang; Shanshan Guo; Kang Fu; Lei Liao; Yi Xu; Siqian Cheng (Environmental Science and Pollution Research, 2020)

Anti-phytopathogen, multi-target acetylcholinesterase inhibitory and antioxidant activities of metabolites from endophytic Chaetomium globosum - Wei Li; Xueqiong Yang; Yabin Yang; Rongting Duang; Guangyi Chen; Xiaozhan Li; Qiling Li; Shaohuan Qin; Shuquan Li; Lixing Zhao; Zhongtao Ding (Natural Product Research, 2016)

Ectopic expression of the Vigna eylindrica ferritin gene enhanced heat tolerance in transgenic wheat (Triticum aestivum L.) - Yanjie Zhao; Xiaoyan Shui; Xueping Wang; Qiling Hou; Baoyun Li; Zhongfu Ni; Qixin Sun; Rongqi Liang (Euphytica, 2016)

A new polyoxygenated farnesylcyclohexenone from Fungus Penicillium sp. - Yabin Yang; Fangfang Yang; Lixing Zhao; Rongting Duang; Guangyi Chen; Xiaozhan Li; Qiling Li; Shaohuan Qin; Zhongtao Ding (Natural Product Research, 2016)

Drought stress tolerance mediated by zinc-induced antioxidative defense and osmotic adjustment in cotton (Gossypium Hirsutum) - Songwei Wu; Chengxiao Hu; Qiling Tan; Lu Li; Kaili Shi; Yong Zheng; Xuecheng Sun (Acta Physiologiae Plantarum, 2015)

A new natural nucleotide and other antibacterial metabolites from an endophytic Nocardia sp. - Wei Li; Xueqiong Yang; Yabin Yang; Shaohuan Qin; Qiling Li; Lixing Zhao; Zhongtao Ding (Natural Product Research, 2015)

A promoter that drives gene expression preferentially in male transgenic rats - Qiling Li; Yamin Ma; Wenzhi Li; Wei Xu; Li Ma; Guoxing Fu; Xiaohua Tian; Yueling Wang; Xu Li; Tameka Bythwood; Jendai Richards; Mukaila A. Akinbami; et al. (Transgenic Research, 2014)